THE INFLUENCE OF SOCIODEMOGRAPHY AND ECONOMIC FACTORS ON THE BEHAVIOR OF REDUCING ELECTRICITY USE IN INDONESIA - Ni Made Sukartini; Okfrisda Sakti (Jurnal Ilmiah Econosains, 2019)
The close relationship between economic and environmental sustainability has led to environmental concerns that have become an interesting topic for research. In an economic view, environmental quality is considered a public good. Savings in electricity usage can reduce household costs and save resources in the electricity production process. This study analyzes the effect of individual characteristics on using electricity. Secondary data from the 2013 Survey Peduli Perilaku Lingkungan Hidup Indonesia (SPPLH) from the Badan Pusat Statistik (BPS) was used in this study. With a total sample of 70406 households covering all regions of Indonesia. The analysis was performed using a binary logistics model. An interesting finding is that an increase in income does not cause individuals to behave in an environmentally conscious manner, in this case reducing electricity usage.